2006
DOI: 10.1194/jlr.m600232-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the structure of the StART domains of MLN64 and StAR proteins in complex with cholesterol

Abstract: Steroidogenic acute regulatory protein-related lipid transfer (StART) domains are ubiquitously involved in intracellular lipid transport and metabolism and other cell-signaling events. In this work, we use a flexible docking algorithm, comparative modeling, and molecular dynamics (MD) simulations to generate plausible three-dimensional atomic models of the StART domains of human metastatic lymph node 64 (MLN64) and steroidogenic acute regulatory protein (StAR) proteins in complex with cholesterol. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
122
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 109 publications
15
122
2
Order By: Relevance
“…Modeling indicates that N-216 MLN64 accommodates a single molecule of cholesterol in this pocket, with the 3 ␤ -OH group coordinated by the two polar residues at the bottom of the pocket. This structure, the crystal structure of the closely related protein StarD4 ( 208 ), and several computational models of StAR (209)(210)(211) are all very similar. Each is characterized by two long ␣ -helixes at the N-and C-termini, two short ␣ -helixes, and a set of nine antiparallel ␤ sheets that form a helix-grip fold ( Fig.…”
Section: Acute Versus Chronic Regulation Ofmentioning
confidence: 76%
“…Modeling indicates that N-216 MLN64 accommodates a single molecule of cholesterol in this pocket, with the 3 ␤ -OH group coordinated by the two polar residues at the bottom of the pocket. This structure, the crystal structure of the closely related protein StarD4 ( 208 ), and several computational models of StAR (209)(210)(211) are all very similar. Each is characterized by two long ␣ -helixes at the N-and C-termini, two short ␣ -helixes, and a set of nine antiparallel ␤ sheets that form a helix-grip fold ( Fig.…”
Section: Acute Versus Chronic Regulation Ofmentioning
confidence: 76%
“…Of particular interest is the observation that genetic ablation of mouse LAMPI and LAMPII, which are both AP-3 cargoes (Bonifacino and Traub, 2003), alters the cellular content of cholesterol detected by filipin staining (Eskelinen et al, 2004). Alternatively, other proteins, such as MLN64, a membrane protein targeted to late endosomes that is predicted to bind cholesterol, based upon structural studies (Alpy et al, 2001;Murcia et al, 2006), could contribute to the phenotypes observed in AP-3 -/-cells. Irrespective of the precise mechanism that leads to reduced cellular cholesterol levels, targeted perturbation of AP-3 complex function might help ameliorate cholesterol accumulation defects seen in a number of disorders, including in NP-C.…”
Section: Journal Of Cell Science 120 (20)mentioning
confidence: 99%
“…The crystal structure of PCTP/StarD2 also shows a hydrophobic tunnel, but in contrast to MLN64/StarD3 and StarD4, it appears to selectively bind phosphatidylcholine (15). More recent modeling studies of the structure of StarD1 and MLN64 have shown that cholesterol appears to be bound by the predicted hydrophobic tunnel of both proteins and reveals changes in the loop at the entrance of the hydrophobic tunnel that may be sufficient for the uptake and release of cholesterol (16).…”
mentioning
confidence: 99%